Role of gut symbionts of insect pests: A novel target for insect-pest control - Rupawate, Pravara S.; Roylawar, Praveen; Khandagale, Kiran; Gawande, Suresh; Ade, Avinash B.; Jaiswal, Durgesh Kumar; Borgave, Seema (Frontiers in Microbiology, 2023)
Insects possess beneficial and nuisance values in the context of the agricultural sector and human life around them. An ensemble of gut symbionts assists insects to adapt to diverse and extreme environments and to occupy every available niche on earth. Microbial symbiosis helps host insects by supplementing necessary diet elements, providing protection from predators and parasitoids through camouflage, modulation of signaling pathway to attain homeostasis and to trigger immunity against pathogens, hijacking plant pathways to circumvent plant defence, acquiring the capability to degrade chemical pesticides, and degradation of harmful pesticides. Therefore, a microbial protection strategy can lead to overpopulation of insect pests, which can drastically reduce crop yield. Some studies have demonstrated increased insect mortality via the destruction of insect gut symbionts; through the use of antibiotics. The review summarizes various roles played by the gut microbiota of insect pests and some studies that have been conducted on pest control by targeting the symbionts. Manipulation or exploitation of the gut symbionts alters the growth and population of the host insects and is consequently a potential target for the development of better pest control strategies. Methods such as modulation of gut symbionts via CRISPR/Cas9, RNAi and the combining of IIT and SIT to increase the insect mortality are further discussed. In the ongoing insect pest management scenario, gut symbionts are proving to be the reliable, eco-friendly and novel approach in the integrated pest management.